DEVELOPMENT OF STUDENTS’ CREATIVITY THROUGH AN INTEGRATIVE PEDAGOGICAL APPROACH - Dekhkambaeva Zulfiya Abubakirovna; Xasanova Maxmuda Tixtayevna; Amangeldiev Alpamis Baxtiyarovich; Kamolova Gulchiroy Otabek qizi (The Bioscan, 2025)
The article presents the results of an experimental pedagogical study on the development of students’ creativity based on an integrative approach. Conducted among 206 university students, the research tested a model that combines cognitive, motivational, and reflective components of learning. Quantitative data verified statistically significant improvements in creative thinking, self-activation, and professional readiness. The study emphasizes that integrative pedagogy enhances flexible thinking, self-reflection, and motivation for innovative learning in the context of Uzbekistan’s educational reforms. KEYWORDS: Creativity, integrative pedagogy, higher education, experimental research, creative competencies, innovative learning, Uzbekistan.